Delineating the clinical spectrum of isolated methylmalonic acidurias: cblA and mut. Issue 1 (15th September 2020) - Hörster, Friederike; Tuncel, Ali Tunç; Gleich, Florian; Plessl, Tanja; Froese, Sean D.; Garbade, Sven F.; Kölker, Stefan; Baumgartner, Matthias R.; ,
Abstract: Introduction: Long‐term outcome is postulated to be different in isolated methylmalonic aciduria caused by mutations in the MMAA gene ( cblA type) compared with methylmalonyl‐CoA mutase deficiency ( mut ), but case definition was previously difficult. Method: Cross‐sectional analysis of data from the European Registry and Network for Intoxication type Metabolic Diseases (Chafea no. December 1, 2010). Results: Data from 28 cblA and 95 mut patients in most cases confirmed by mutation analysis (including 4 new mutations for cblA and 19 new mutations for mut ). Metabolic crisis is the predominant symptom leading to diagnosis in both groups. Biochemical disturbances during the first crisis were similar in both groups, as well as the age at diagnosis. Z scores of body height and body weight were similar in both groups at birth, but were significantly lower in the mut group at the time of last visit. Glomerular filtration rate was significantly higher in cblA ; and as a consequence, chronic renal failure and related complications were significantly less frequent and renal function could be preserved even in older patients. Neurological complications were predominantly found in the mut subgroup. Methylmalonic acidemia (MMA) levels in urine and plasma were significantly lower in cblA. 27/28 cblA patients were reported to be responsive to cobalamin, only 86% of cblA patients were treated with i.m. hydroxocobalamin. In total, 73% of cblA and 98% of mut patients followed a calculated diet with amino acid supplements in 27% ( cblA ) and 69% ( mut ). During the study interval, six patients from the mut group died, while all cblA patients survived. Conclusion: Although similar at first, cblA patients respond to hydroxocobalamin treatment, subsequently show significantly lower levels of MMA and a milder course than mut patients.